Young people's voices: Insights to reduce inequality in education in urban Latin America - Ann Mitchell; Pablo Del Monte; Séverine Deneulin (University of Bath, Centre for Development Studies (CDS), 2016)
The aim of this paper is to illustrate how gaining a greater understanding of young people's values can contribute to the design of more effective educational policies in urban marginal neighbhourhoods using the capability approach as a normative framework of analysis. It is based on fieldwork carried out in one of the City of Buenos Aires' largest and oldest informal settlements (or villas): the villa 1-11-14 of Bajo Flores. The research is motivated by the markedly inferior educational and employment outcomes of young people who live in the villas in relation to the rest of the city, the country's expanding problem of drugs, and the generalized perception in society of young people as perpetrators of violence. In order to have a better understanding of the factors behind inferior schooling outcomes in urban peripheral communities, and so design more appropriate policies, the paper draws on qualitative data collected through individual semi-structured interviews with young men and women to analyse what they value most in their lives, and how they value secondary education. The research underlines both the negative influence of contextual factors and the critical role of significant others, including family members and teachers, in providing emotional support and giving young people a sense of purpose in life and a reason to value secondary education. These findings suggest the need for more integral educational policies that transcend the provision of access to secondary school.
Keywords: 330; Youth; capability approach; secondary education; urban marginality; Latin America